Evaluation of The COVID-19 Vaccination Program for the Elderly in the Rawalo Health Center With the CIPP (Context, Input, Process, and Product) Model (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2023)
Rawalo sub-district had a relatively high number of COVID-19 cases compared to other sub-districts in Banyumas Regency. The government provides COVID-19 vaccination which aims to reduce the number of COVID-19 cases by forming Herd Immunity in the community. The elderly are a group at high risk of morbidity and mortality due to exposure to COVID-19. However, the coverage of COVID-19 vaccination for the elderly at the Rawalo Health Center is still relatively low. This study was aimed to evaluate the program with the CIPP (Context, Input, Process, Product) model in a complex and comprehensive manner regarding how the implementation of the COVID-19 vaccination program in the elderly. This research was a qualitative study with a descriptive approach using observation and in-depth interview methods selected by purposive sampling technique. The research subjects as the main informants included the Head of the Puskesmas, the Head of the COVID-19 Vaccination Program Team, the COVID-19 Vaccination Coordinator and health cadres. Meanwhile, the elderly group and the Banyumas Regency Health Office as triangulation informants. The results showed that vaccination coverage in the elderly was still low, at 10% for dose 3. This was due to less thorough education, lack of human resources (vaccination officers), and ineffective coordination, there is data that is not synchronous or valid. There are technical and non-technical obstacles in recording and reporting. Thus, improvements need to be made to aspects that affect the vaccination implementation process and low coverage.